Longitudinal change in parent and child functioning after internet-delivered cognitive-behavioral therapy for chronic pain. Issue 10 (October 2017) - Law, Emily F.; Fisher, Emma; Howard, Waylon J.; Levy, Rona; Ritterband, Lee; Palermo, Tonya M.
Abstract : Abstract: Theoretical models of pediatric chronic pain propose longitudinal associations between children's pain experiences and parent and family factors. A large body of cross-sectional research supports these models, demonstrating that greater parent distress and maladaptive parenting behaviors are associated with greater child disability. Family-based cognitive-behavioral therapy interventions have been developed for youth with chronic pain which aim to improve child disability and reduce maladaptive parenting behaviors. However, little is known about temporal, longitudinal associations between parent and child functioning in this population. In the present study, we conducted a secondary analysis of data from 138 families of youth with chronic pain aged 11 to 17 years old who received family-based cognitive-behavioral therapy delivered through the Internet as part of a randomized controlled trial. Measures of child disability, parent protective behavior, and parent distress were obtained at pretreatment, immediate posttreatment, 6-month follow-up, and 12-month follow-up. Latent growth modeling indicated that child disability, parent protective behavior, and parent distress improved with treatment over the 12-month study period. Latent growth modeling for parallel processes indicated that higher parent distress at pretreatment predicted less improvement in child disability over 12 months. No other predictive paths between parent and child functioning were significant. These findings indicate that parent distress may increase the risk of poor response to psychological pain treatment among youth with chronic pain. At present, parent distress is not routinely targeted in psychological interventions for pediatric chronic pain. Research is needed to determine optimal strategies for targeting parent and family factors in the treatment of pediatric chronic pain. Abstract : High parent distress at pretreatment predicts less improvement in child disability over 12 months after Internet-delivered cognitive-behavioral therapy for chronic pain management.